Understanding the link between socioeconomic status and belief in fake news: The mediating role of uncertainty avoidance - Vilar, Jose Gabriel D. (Animo Repository, 2022)
The 2022 Philippine elections gave way to a distressing rise of fake news purposely created to mislead and deceive social media users. This article reviews current literature on fake news and what could potentially explain its prevalence. To understand the cultural factors which weaken defenses against fake news, factors such as Socioeconomic status and Uncertainty avoidance according to Hofstede’s model of cultural dimensions were tested. The sample consisted of BBM voters, between the ages of 18 - 24 years old (N= 171). A quasi-experimental design was used and the variables were measured via a mediation analysis to test how uncertainty avoidance as a mediating variable predicted the relationship between SES and belief in fake news. The results showed that Uncertainty avoidance did not have a significant mediating role between SES and belief in fake news as consistently high levels of UA were observed across the population as SES is not a predictor of UA levels. SES however was able to predict how individuals perceive and discern fake news as individuals from higher socioeconomic backgrounds are able to accurately identify fake news from real news as compared to those from lower socioeconomic backgrounds implying that the cultural identity of socioeconomic status influences the way individuals respond to fake news. This reveals another avenue where those from a lower socioeconomic background are further disadvantaged in the Philippines. This needs to be brought to the attention of government agencies concerned as we live in a digital world, and the ability to navigate fake news and possess critical thinking skills necessary with access to a social media platform is imperative. Keywords: fake news, socioeconomic status, uncertainty avoidance, Hofstede's cultural dimensions, theory of motivated reasoning, social media.